Giáo trình lập trình web với java (đĩa) - Nhóm phát triển p hần mềm sinh viên học sinh-SSDG (SSDG, 2007)
The Java language has been growing from strength to strength since its inception in 1995. It has since proved to be both powerful and extraordinarily easy to learn and use. This is what makes it ideal for the beginner. With dramatic changes to the handling of files, and the introduction of native support for XML, Java has been updated to work faster and to be current with the incredible rise of XML as a medium for communicating data.